2019
DOI: 10.1088/1361-6463/aaf941
|View full text |Cite
|
Sign up to set email alerts
|

Impact of trap states on inductive phenomena in 30% InGaN/GaN MQW LED devices

Abstract: Investigation of structural quality (by x-ray diffraction) and analysis of defects and interfaces in epitaxial layers (by transmission electron microscopy (TEM)) have been performed on InGaN/ GaN multiple quantum wells (MQWs) LED structure. Using energy dispersive x-ray analysis attached to the TEM system, 30% indium content in the InGaN well was measured. For electrooptic analysis, 30% in content InGaN/GaN MQWs LED in the p-i-n structure was analyzed through admittance spectroscopy and photo/electroluminescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…A significant amount of research has focused on elucidating the mechanism of NC. Numerous sources of NC have been proposed for various electronic devices, such as organic light-emitting diodes (OLEDs) [2,3,[5][6][7][8][9][10][11], inorganic light-emitting diodes [12][13][14], and Schottky barrier diodes (SBDs) [15][16][17][18][19]. We previously demonstrated that self-heating in electronic devices is a source of NC, considering an OLED * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…A significant amount of research has focused on elucidating the mechanism of NC. Numerous sources of NC have been proposed for various electronic devices, such as organic light-emitting diodes (OLEDs) [2,3,[5][6][7][8][9][10][11], inorganic light-emitting diodes [12][13][14], and Schottky barrier diodes (SBDs) [15][16][17][18][19]. We previously demonstrated that self-heating in electronic devices is a source of NC, considering an OLED * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%